2019
DOI: 10.1108/ijoa-07-2018-1475
|View full text |Cite
|
Sign up to set email alerts
|

The barriers and enablers to career and leadership development

Abstract: Purpose The purpose of this study is to contrast how the relationship between career and leadership development and workplace culture is experienced by women in two different countries and the implications this has for human resource development initiatives. Design/methodology/approach The study used a qualitative narrative research design to understand how the lived experiences of Australian and Vietnamese early- to mid-career female academics is engendered. Findings The study identified a number of key b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…During each 40-minute working group session, participants were divided into breakout rooms to discuss the following topics: (1) Strengthening Networks, (2) Building Essential Skills, (3) Authentic/Inclusive Leadership, (4) Building Job-Seeking Skills, (5) Mentorship. The focus areas were chosen based on previous literature that described various barriers to women’s leadership in relevant fields [ 12 13 ]. We asked participants to discuss their assigned topics, specifically focusing on how institutions can better support emerging women leaders in global health, and asked one person from each group to take notes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During each 40-minute working group session, participants were divided into breakout rooms to discuss the following topics: (1) Strengthening Networks, (2) Building Essential Skills, (3) Authentic/Inclusive Leadership, (4) Building Job-Seeking Skills, (5) Mentorship. The focus areas were chosen based on previous literature that described various barriers to women’s leadership in relevant fields [ 12 13 ]. We asked participants to discuss their assigned topics, specifically focusing on how institutions can better support emerging women leaders in global health, and asked one person from each group to take notes.…”
Section: Methodsmentioning
confidence: 99%
“…Barriers to women’s leadership in different countries and settings have been well established in the literature at the individual and institutional levels [ 12 13 ]. Lack of mentorship, workplace power imbalances, work-home responsibility imbalance, and gender bias may occur at each career stage for women and affect career advancement [ 14 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vietnamese women are under-represented for senior roles in prestigious organizations compared to other countries (Pham, 2019). To the best of our knowledge, till now, only seven studies have been done in Vietnam on this topic (Hong, 2018;Kelly, 2011;Lazarian-Chehab, 2017;Mate et al, 2019;Nguyen, 2013;Soryaly and Khon, 2017;Dang, 2017).…”
Section: Review Of Studies In Women Leadership In Higher Education (Wlhe)mentioning
confidence: 99%
“…Previous research showed that more men hold professorship than women (Camacci et al, 2020). Based on literature studies, female lecturers consider the importance of balancing life and work (work-life balance) by doing all household affairs and pursuing a career (Mate et al, 2019).…”
Section: Gap Analysis Of Lecturer Career Advancement In the Usa And Australiamentioning
confidence: 99%